Preparation method of low-deformation high-temperature-resistant frequency-selective conformal antenna housing
Through the quartz fiber and carbon fiber-reinforced benzoxazine resin prepreg and laser etching technology, the deformation problem of conformal frequency selection radome at high temperature is solved, the low deformation characteristics and frequency selection function are achieved, and the aircraft is improved Stealth and communication performance.
Patent Information
- Application Number
- CN202411564820.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-14
AI Technical Summary
The existing conformal frequency selection radome has poor temperature resistance in high temperature environments and is prone to deformation and thermal deformation, affecting the stealth and communication performance of the aircraft.
Using quartz fiber and carbon fiber reinforced benzoxazine resin prepreg, a low-deformed frequency selection layer is formed by cutting and thermal curing, and laser etching and chemical deposition of conductive metals are carried out in the wave-transmitting window area to form a frequency selection function. The outer skin is then heat-pressed and milled.
The low deformation characteristics at high temperatures above 400℃ are achieved, ensuring the stealth and communication performance of the aircraft, with a deformation rate less than three thousandths, and the frequency selection pattern is generated, so that the aircraft has good stealth and communication performance.
Smart Images

Figure CN119305222A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of antenna cover preparation, and more specifically, to a method for preparing a low-deformation, high-temperature-resistant, frequency-selective conformal antenna cover. Background Art
[0002] The radome is an important component of the antenna on an aircraft. It not only needs to be conformally integrated with the surface structure of the aircraft to ensure the aerodynamic operation function of the aircraft, but also needs to protect the antenna components inside the radome from external airflow, wind, frost, rain, snow, dust and other adverse factors; in addition, as a window for the antenna to transmit and receive electromagnetic signals, an auxiliary antenna is also needed to achieve stealth function.
[0003] The radome itself reflects enemy radar waves very weakly, but the antenna inside it is one of the main scattering sources of the aircraft; when the electromagnetic wave enters the radome, it will be reflected multiple times by the antenna and high-frequency components, and will produce a strong echo in the direction of the target's head.
[0004] Therefore, in order to achieve the stealth function of the aircraft, measures must be taken on the radome to scatter enemy radar waves to other directions while allowing one's own radar waves to be transmitted efficiently.
[0005] At present, the key technology to achieve stealth outside the electromagnetic window band and within the wave transmission band is frequency selective surface technology (frequency selective); the frequency selective antenna cover that is conformal to the aircraft surface has a vital impact on the communication, stealth and other performances of the aircraft.
[0006] At present, as the flight speed of aircraft is getting faster and faster, some aircraft even fly at a speed of more than Mach 10. At the same time, as the information functions of aircraft become more and more abundant, the power of their antennas is also getting larger and larger, which leads to higher requirements for the temperature resistance of the conformal radome on the surface of the aircraft. However, the current conformal frequency-selective radome is mainly prepared by using resin-based prepregs such as cyanate, epoxy, and bismaleimide, and a flexible frequency-selective film is mixed in the middle. However, this structure and preparation process have the following problems:
[0007] 1. Cyanate ester, epoxy and other resins generally have poor temperature resistance, and few resins can withstand temperatures above 400°C;
[0008] 2. The curing shrinkage rate of high temperature resistant resins such as polyimide, phthalonitrile, and silicon aryl acetylene is relatively large, which may easily cause obvious warping deformation of the entire antenna cover;
[0009] 3. The curing temperature of high temperature resistant resins such as polyimide, phthalonitrile, and silicon aryl acetylene is relatively high, often close to its glass transition temperature. When it can withstand high temperatures above 400°C, its curing temperature is often as high as around 350°C. This results in greatly different thermal deformations between the molding mold and the antenna cover, resulting in serious deformation of the antenna cover.
[0010] 4. High-temperature-resistant resins often exhibit high rigidity and cannot be used to prepare flexible frequency-selective films. Conventional frequency-selective films such as PI will not only increase the heterogeneous components in the antenna cover, resulting in deterioration of mechanical properties such as shear between antenna covers, but are also easily damaged at high temperatures and lose frequency-selective performance, thereby affecting the communication, stealth and other performances of the aircraft.
[0011] Therefore, there is an urgent need to develop a method for preparing a low-deformation, high-temperature resistant, frequency-selective antenna cover to meet the development needs of ultra-high-speed flight and high surface conformality of aircraft. Summary of the invention
[0012] The technical problem to be solved by the present invention is to provide a method for preparing a low-deformation, high-temperature-resistant, frequency-selective conformal radome, which can effectively solve the problems in the prior art that the radome is not resistant to high temperatures, has large deformation, and the factors of the embedded frequency-selective film affect the overall strength and stealth performance of the radome;
[0013] The solution adopted by the present invention to solve the technical problem is:
[0014] A method for preparing a low-deformation, high-temperature-resistant, frequency-selective conformal radome comprises the following steps:
[0015] Step S1: preparing a resin glue solution with low deformation and high temperature resistance function;
[0016] Step S2: preparing quartz fiber reinforced benzoxazine resin prepreg and carbon fiber reinforced benzoxazine resin prepreg;
[0017] Step S3: cutting the quartz fiber reinforced benzoxazine resin prepreg according to the shape of the radome to obtain a ply A corresponding to the overall contour of the radome and a ply B corresponding to the wave-transmitting window area; cutting the carbon fiber reinforced benzoxazine resin prepreg according to the shape of the radome to obtain a ply C corresponding to the flange area;
[0018] Step S4: Laying down layers A, B and C on the radome forming steel mold until the frequency-selective layer is located to form product A, and thermally curing product A to obtain an outer skin semi-cured part;
[0019] Step S5: treating the layer B at the wave-transmitting window region carrying the frequency-selective pattern to make its surface rough, preparing an activation film on the surface, and laser-etching the activation film according to the requirements of the frequency-selective pattern to form a laser-etched region in the shape of the frequency-selective pattern;
[0020] Step S6: removing the activation film, chemically depositing a conductive metal on the laser-etched area to form a conductive layer in a frequency-selective pattern, and obtaining an outer skin having a frequency-selective layer;
[0021] Step S7: continue to lay up ply A, ply B and ply C on the outer skin with the frequency-selective layer to form product B, and perform hot pressing and curing on product B to obtain a blank;
[0022] Step S8: Milling the blank to shape it, drilling the mounting holes, and completing the preparation.
[0023] In some possible implementations, the resin glue includes phenol / diaminodiphenylmethane type benzoxazine monomer, phenol / aldehyde type benzoxazine monomer, bisphenol A type epoxy resin and acetone solvent.
[0024] In some possible implementations, the step S1 specifically refers to:
[0025] Mix 8% to 16% by weight of phenol / diaminodiphenylmethane type benzoxazine monomer, 12% to 25% by weight of phenol / aldehyde type benzoxazine, 3% to 8% by weight of bisphenol A type epoxy resin, and 40% to 60% by weight of acetone solvent, and stir evenly;
[0026] The stirring speed is 100 to 500 revolutions per minute.
[0027] The stirring time is 10 minutes to 30 minutes, so that it can withstand high temperatures above 400°C, the deformation rate is less than 0.3%, and it has good viscosity, making it suitable for autoclave molding.
[0028] In some possible implementations, step S2 specifically refers to:
[0029] The QW100 quartz fiber cloth and the T300 carbon fiber cloth are fully impregnated in the resin glue solution respectively;
[0030] Air-drying or drying in an oven to remove the acetone solvent, and preparing quartz fiber reinforced benzoxazine resin prepreg and carbon fiber reinforced benzoxazine resin prepreg;
[0031] Among them, the drying temperature is 30°C to 60°C, and the drying time is 12h to 36h.
[0032] In some possible implementations, the thermal curing of the product A in step S4 specifically refers to:
[0033] Layer a porous isolation cloth, a non-porous isolation cloth and a breathable felt on the product A, seal the formed structure on the mold, place it in an autoclave for pre-pressing, and obtain an outer skin semi-cured part;
[0034] Among them, the curing temperature is 120℃~160℃, and the curing time is 6h;
[0035] The curing pressure is 0.3MPa~0.6MPa;
[0036] The vacuum degree of the autoclave is 0~0.1MPa.
[0037] In some possible implementations, when the activation film is laser etched in step S5, the laser light source is a near-infrared laser, the laser power is 20W to 600W, the pulse repetition frequency is 10Hz to 400KHz, the number of processing times is 2 to 6 times, the scanning speed is 5mm / s to 5000mm / s, and the scanning spacing is 0.006mm to 0.5mm.
[0038] In some possible implementations, step S6 specifically refers to: cleaning and removing the activation film, placing the laser-etched outer skin solidified part in a chemical plating solution, and depositing the conductive metal in the chemical plating solution to the laser-etched area of the antenna cover outer skin wave-transmitting window; wherein, metallic copper is first deposited in the laser-etched area, and then the gold layer is deposited.
[0039] In some possible implementations, the step S7 of hot pressing and curing the product B specifically refers to:
[0040] Sequentially lay a peelable cloth and a breathable felt on the product B, seal the formed structure on a mold, and place it in an autoclave for pre-pressing to obtain a blank;
[0041] Among them, the curing temperature is 120℃~200℃, and the curing time is 10h;
[0042] The curing pressure is 0.1MPa~0.8MPa;
[0043] The vacuum degree of the autoclave is 0~0.1MPa.
[0044] In some possible implementations, the fiber orientation angles of the fibers in ply A, ply B, and ply C in the blank are 0° or 90°.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] The conformal radome prepared by the present invention has good resistance to high temperatures above 400°C, a deformation rate of ≤3‰, and the pattern of the frequency-selective layer is generated natively on the ply B, so that the aircraft has good stealth and communication performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 It is a work flow chart of the present invention;
[0048] Figure 2 A top view of the connection between ply B and ply C in the present invention;
[0049] Figure 3This is a structural diagram of Example 1;
[0050] Figure 4 It is a structural view of Example 2;
[0051] Among them: 1. Layer A; 2. Layer B; 3. Layer C; 4. Frequency selection layer. DETAILED DESCRIPTION
[0052] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral body; it can be directly connected, or indirectly connected through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. The "first", "second" and similar words mentioned in this application do not indicate any order, quantity or importance, but are only used to distinguish different components. Similarly, "one" or "one" and other similar words do not indicate a quantity restriction, but indicate the existence of at least one. In the implementation of this application, "and / or" describes the association relationship of the associated objects, indicating that there can be three relationships, for example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In the description of the embodiments of the present application, unless otherwise specified, the meaning of "multiple" refers to two or more. For example, multiple positioning columns refer to two or more positioning columns. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0053] The present invention is described in detail below.
[0054] Embodiment 1:
[0055] like Figure 1 , Figure 2 , Figure 3 As shown: A method for preparing a low-deformation, high-temperature resistant, frequency-selective conformal radome, the radome having a frequency-selective layer; specifically comprising the following steps:
[0056] Step S1: preparing a resin adhesive with low deformation and high temperature resistance; the resin adhesive comprises phenol / diaminodiphenylmethane type benzoxazine monomer, phenol / aldehyde type benzoxazine monomer, bisphenol A type epoxy resin and acetone solvent.
[0057] The preparation specifically refers to: mixing 8% to 16% by weight of phenol / diaminodiphenylmethane type benzoxazine monomer, 12% to 25% by weight of phenol / aldehyde type benzoxazine, 3% to 8% by weight of bisphenol A type epoxy resin, and 40% to 60% by weight of acetone solvent, and stirring them evenly;
[0058] Wherein, during stirring, the blending speed is 400 revolutions / min, and the time is 10min to 30min;
[0059] Step S2: preparing quartz fiber reinforced benzoxazine resin prepreg and carbon fiber reinforced benzoxazine resin prepreg; specifically, it refers to:
[0060] The QW100 quartz fiber cloth and the T300 carbon fiber cloth are fully impregnated in the resin glue solution respectively;
[0061] Air-drying or drying in an oven to remove the acetone solvent, and preparing quartz fiber reinforced benzoxazine resin prepreg and carbon fiber reinforced benzoxazine resin prepreg;
[0062] Among them, the drying temperature is 30°C to 60°C, and the drying time is 12h to 36h.
[0063] Step S3: According to the shape of the radome Figure 2 As shown, the quartz fiber reinforced benzoxazine resin prepreg is cut to obtain a ply A corresponding to the overall contour of the radome and a ply B corresponding to the wave-transmitting window area; the carbon fiber reinforced benzoxazine resin prepreg is cut according to the shape of the radome to obtain a ply C corresponding to the flange area;
[0064] Specifically, the ply A is 10 layers, the ply B is 8 layers, and the ply C is 10 layers; when stacking, the ply B will be located in the installation area formed by the ply C;
[0065] Step S4: Laying down layers A, B and C on the radome forming steel mold until the frequency-selective layer is located to form product A, and thermally curing product A to obtain an outer skin semi-cured part;
[0066] The specific steps include:
[0067] Step S41: First, two layers of plies A, two layers of plies B, and one layer of ply C are sequentially stacked on the radome forming steel mold with positioning holes; the two layers of plies B will be located inside the ply C to form a layer structure, and the layer structure will be stacked on the ply A;
[0068] Step S42: Subsequently, two layers of plies A, two layers of plies B, and one layer of ply C are sequentially stacked again on the formed one-layer structure, and the two layers of plies B will be located inside the ply C to form a one-layer structure;
[0069] Step S43: stacking a layer of ply A on the layer of structure formed in step S42 to form product A;
[0070] Step S44: sequentially laying a porous isolation cloth, a non-porous isolation cloth and a breathable felt on the layer A laid in step S43, sealing the formed structure on the mold, placing it in an autoclave for pre-pressing, and obtaining an outer skin semi-cured part; wherein the curing temperature is 120° C. to 160° C., and the curing time is 6 hours;
[0071] The curing pressure is 0.3MPa~0.6MPa; the vacuum degree of the autoclave is 0.08~0.1MPa.
[0072] Furthermore, during curing, the curing is first performed at a temperature of 120°C for two hours; then the curing temperature is adjusted to 140°C for fixing, and the curing time is two hours; finally, the curing temperature is adjusted to 160°C, and the curing time is two hours;
[0073] Step S5: treating the layer B at the wave-transmitting window region carrying the frequency-selective pattern to make its surface rough, preparing an activation film on the surface, and laser-etching the activation film according to the requirements of the frequency-selective pattern to form a laser-etched region in the shape of the frequency-selective pattern;
[0074] Specifically, the wave-transmitting window area of the outer skin semi-cured part carrying the frequency-selective pattern is pre-treated by resin repair, scraping and grinding excess materials to make it flat, smooth and free of defects;
[0075] Then, a laser activated material glue is prepared, and the laser activated glue is evenly pre-placed on the surface of the outer skin window area (inward direction) so that an activated film is formed on the inner surface of the outer skin semi-cured part after a period of time; finally, a near-infrared laser is used to laser-etch the activated film according to the frequency-selective pattern requirements to form a laser-etched area in the shape of a frequency-selective pattern;
[0076] When the activated film is laser etched, the laser light source is a near-infrared laser, the laser power is 20W to 600W, the pulse repetition frequency is 10Hz to 400KHz, the processing times are 2 to 6 times, the scanning speed is 5mm / s to 5000mm / s, and the scanning spacing is 0.006mm to 0.5mm.
[0077] Step S6: removing the activation film, chemically depositing a conductive metal on the laser-etched area to form a conductive layer in a frequency-selective pattern, and obtaining an outer skin having a frequency-selective layer;
[0078] Step S6 specifically refers to: cleaning and removing the activation film, placing the laser-etched outer skin solidified part in a chemical plating solution, and depositing the conductive metal in the chemical plating solution to the laser-etched area of the antenna cover outer skin wave-transmitting window; wherein, metallic copper is first deposited in the laser-etched area, and then the gold layer is deposited.
[0079] Step S7: continue to lay up ply A, ply B and ply C on the outer skin with the frequency-selective layer to form product B, and perform hot pressing and curing on product B to obtain a blank;
[0080] The specific steps include:
[0081] Step S71: when laying on the outer skin, two layers of plies C, one layer of ply A, one layer of ply C, and two layers of ply B are laid in sequence, and one layer of ply and two layers of ply B form a layer structure;
[0082] Step S72: Lay two layers of ply A on the one-layer structure formed in step S71, and then lay two layers of ply B and one layer of ply C; one layer of ply C and two layers of ply B form a one-layer structure;
[0083] Step S73: Laying two layers of layer A, two layers of layer A, and then two layers of layer C on the layer structure formed in step S72 to form product B;
[0084] Step S74: Laying the peelable cloth and the breathable felt on the product B in sequence, sealing the formed structure on the mold, placing it in an autoclave for pre-pressing, and obtaining a blank;
[0085] Among them, the curing temperature is 120℃~200℃, and the curing time is 10h;
[0086] The curing pressure is 0.08MPa~0.1MPa; the vacuum degree of the autoclave is 0.1MPa;
[0087] Furthermore, during the curing, the curing is divided into five stages, each of which takes two hours, and the temperature of the five stages is increased gradually, specifically, first, curing at a temperature of 120°C for two hours; adjusting the curing temperature to 140°C for two hours; adjusting the curing temperature to 160°C for two hours; adjusting the curing temperature to 180°C for two hours; adjusting the curing temperature to 200°C for two hours;
[0088] Step S8: Milling the blank to shape it, drilling the mounting holes, and completing the preparation.
[0089] Furthermore, the fiber orientation angles of the fibers in plies A, B and C in the blank are 0° or 90°. This setting avoids the problem of serious deformation of the final radome caused by angles between the fibers between the plies.
[0090] Example 2: As shown in the figure Figure 1 , Figure 2 , Figure 4 As shown, the preparation method of the high temperature resistant antenna cover with double frequency selective layers specifically comprises the following steps:
[0091] Step 1: Dissolve phenol / diaminodiphenylmethane benzoxazine monomer, phenol / aldehyde benzoxazine monomer, and bisphenol A epoxy resin in acetone solvent and stir thoroughly to form a resin glue. The resin glue plays a decisive role in the curing behavior, thermodynamic properties, and processability of the radome. The components of the resin glue are as follows:
[0092] Phenol / diaminodiphenylmethane type benzoxazine monomer 8% to 16%;
[0093] Phenol / aldehyde type benzoxazine monomer 12% to 25%;
[0094] Bisphenol A epoxy resin 3% to 8%;
[0095] Acetone solvent 40% to 60%;
[0096] During stirring, the blending speed was 400 rpm and the stirring time was 30 min;
[0097] Step 2: fully immerse the QW100 quartz fiber cloth and the T300 carbon fiber cloth in the glue solution, and then remove the acetone solvent by air drying and drying, and dry to obtain the latter two prepregs, namely, quartz fiber reinforced benzoxazine resin prepreg and carbon fiber reinforced benzoxazine resin prepreg; wherein the drying temperature is 60° C. and the drying time is 24 hours;
[0098] Step 3: Follow the instructions Figure 3 Top view, cut according to the shape of the entire radome, ply A with ten layers, ply B with twelve layers, and ply C with eight layers; the fibers in all plies are required to have the same orientation, with an angle of 0°. If there is an angle between the fibers of the plies, the overall deformation of the radome will be serious.
[0099] Step 4: stack two layers of ply A, two layers of ply B, one layer of ply C, and two layers of ply A in sequence on the radome forming steel mold with positioning holes; the two layers of ply B and one layer of ply C form a layer structure;
[0100] Then, two layers of ply B, one layer of ply C, and one layer of ply A are stacked in sequence; two layers of ply B and one layer of ply C form a layer structure;
[0101] Step 5: On the product formed in step 4, a porous isolation cloth, a non-porous isolation cloth and a breathable felt are sequentially laid, and the product is sealed on the mold with a vacuum bag, and then placed in an autoclave for pre-pressing to obtain a semi-cured outer skin. During curing, the curing is divided into three stages, wherein the initial curing temperature is 120°C and the fixed time is 2h; then the temperature is raised to 140°C and the fixed time is 2h, and then the temperature is raised to 160°C and the fixed time is 2h; the curing pressure is 0.6MPa; the vacuum degree during the curing process is 0.08-0.1MPa.
[0102] Step 6: Pre-treat the wave-transmitting window area of the outer skin semi-cured part carrying the frequency-selective pattern by resin repair, scraping and grinding the excess materials, so that it is flat, smooth and defect-free, and its surface roughness reaches Ra3.2;
[0103] Then, a laser activated material glue is prepared and uniformly pre-placed on the surface of the window area of the outer skin (inwardly) so that a laser activated film is formed on the inner surface of the outer skin semi-cured part after a period of time;
[0104] The laser activated material colloidal solution is a copper phosphate solution, to which a suitable amount of surfactant is added to enhance the wettability of the laser activated material colloidal solution and the substrate. The thickness of the laser activated material colloidal solution after being dried and formed into a film is 0.2 mm.
[0105] Finally, a near-infrared laser is used to laser-etch the activation film according to the frequency-selective pattern requirements to form a laser-etched area in the shape of a frequency-selective pattern; the laser power is 400 W, the pulse repetition frequency is 300 KHz, the scanning speed is 2000 mm / s, the scanning spacing is 0.1 mm, and the processing times are 3 times;
[0106] Step 7: Clean and remove the laser activated film, then place the laser-etched outer skin in a chemical plating solution to deposit the conductive metal in the chemical plating solution to the laser-etched area of the wave-transmitting window of the outer skin of the radome; first, deposit a 20-micron thick copper layer on the laser-etched area, and then deposit a 1-micron thick gold layer;
[0107] Step 8: Lay four layers of ply B and two layers of ply C in sequence on the radome forming steel mold with positioning holes.
[0108] Step 9: On the product processed in step 8, porous isolation cloth, non-porous isolation cloth and breathable felt are sequentially laid, and the vacuum bag is sealed on the mold with a sealing putty strip, and then placed in an autoclave for pre-pressing to obtain an outer skin; during curing, the curing is divided into three stages, wherein the initial curing temperature is 120°C and the fixed time is 2h; then the temperature is raised to 140°C and the fixed time is 2h, and then the temperature is raised to 160°C and the fixed time is 2h; the curing pressure is 0.6MPa; the curing vacuum is 0.08~0.1MPa.
[0109] Step S10: pre-treating the wave-transmitting window area of the outer skin semi-cured part carrying the frequency-selective pattern by resin repair, scraping and grinding the excess material, so that it is flat, smooth and defect-free, and its surface roughness reaches Ra3.2;
[0110] Then, a laser activated material glue is prepared and uniformly pre-placed on the surface of the window area of the outer skin (inwardly) so that a laser activated film is formed on the inner surface of the outer skin semi-cured part after a period of time;
[0111] The laser activated material colloidal solution is a copper phosphate solution, to which a suitable amount of surfactant is added to enhance the wettability of the laser activated material colloidal solution and the substrate. The thickness of the laser activated material colloidal solution after being dried and formed into a film is 0.2 mm.
[0112] Finally, a near-infrared laser is used to laser-etch the activation film according to the frequency-selective pattern requirements to form a laser-etched area in the shape of a frequency-selective pattern; the laser power is 400 W, the pulse repetition frequency is 300 KHz, the scanning speed is 2000 mm / s, the scanning spacing is 0.1 mm, and the processing times are 3 times;
[0113] Step 11: Clean and remove the laser activated film, then place the laser-etched outer skin in a chemical plating solution, so that the conductive metal in the chemical plating solution is deposited on the laser-etched area of the wave-transmitting window of the outer skin of the radome; first, deposit a 20-micron thick copper layer on the laser-etched area, and then deposit a 1-micron thick gold layer;
[0114] Step 12: Continue to lay prepreg on the outer skin with the frequency-selective layer: lay one layer of ply A, two layers of ply B, one layer of ply C, and one layer of ply A in sequence; two layers of ply B and one layer of ply C form a layer structure;
[0115] Stack one layer of ply A, two layers of ply B, and one layer of ply C again; two layers of ply B and one layer of ply C form a layer structure;
[0116] Finally, two layers of ply A and two layers of ply C are laid in sequence;
[0117] After the prepreg is laid out according to the overall layering configuration of the antenna cover, the peelable cloth and breathable felt are laid in sequence, and the vacuum bag is sealed on the mold with a sealing putty strip, and then placed in an autoclave for hot pressing. During curing, first cure at 120°C for two hours; adjust the curing temperature to 140°C for fixing, and the curing time is two hours; adjust the curing temperature to 160°C, and the curing time is two hours; adjust the curing temperature to 180°C, and the curing time is two hours; adjust the curing temperature to 200°C, and the curing time is two hours; the curing pressure is 0.6MPa; the vacuum degree is 0.1MPa.
[0118] Step 13: Mill the frequency-selective antenna cover blank and drill the mounting holes.
[0119] The present invention is not limited to the above-mentioned specific embodiments, but extends to any new features or any new combination disclosed in this specification, as well as any new method or process steps or any new combination disclosed.
Claims
1. A method for preparing a low-deformation, high-temperature-resistant, frequency-selective conformal radome, characterized in that: The specific steps include: Step S1: preparing a resin glue solution with low deformation and high temperature resistance function; Step S2: preparing quartz fiber reinforced benzoxazine resin prepreg and carbon fiber reinforced benzoxazine resin prepreg; Step S3: cutting the quartz fiber reinforced benzoxazine resin prepreg according to the shape of the radome to obtain a ply A corresponding to the overall contour of the radome and a ply B corresponding to the wave-transmitting window area; cutting the carbon fiber reinforced benzoxazine resin prepreg according to the shape of the radome to obtain a ply C corresponding to the flange area; Step S4: Laying down layers A, B and C on the radome forming steel mold until the frequency-selective layer is located to form product A, and thermally curing product A to obtain an outer skin semi-cured part; Step S5: treating the layer B at the wave-transmitting window region carrying the frequency-selective pattern to make its surface rough, preparing an activation film on the surface, and laser-etching the activation film according to the requirements of the frequency-selective pattern to form a laser-etched region in the shape of the frequency-selective pattern; Step S6: removing the activation film, chemically depositing a conductive metal on the laser-etched area to form a conductive layer in a frequency-selective pattern, and obtaining an outer skin having a frequency-selective layer; Step S7: continue to lay up ply A, ply B and ply C on the outer skin with the frequency-selective layer to form product B, and perform hot pressing and curing on product B to obtain a blank; Step S8: Milling the blank to shape it, drilling the mounting holes, and completing the preparation.
2. The method for preparing a low-deformation, high-temperature-resistant, frequency-selective conformal radome according to claim 1, characterized in that: The resin glue comprises phenol / diaminodiphenylmethane type benzoxazine monomer, phenol / aldehyde type benzoxazine monomer, bisphenol A type epoxy resin and acetone solvent.
3. The method for preparing a low-deformation, high-temperature-resistant, frequency-selective conformal radome according to claim 2, characterized in that: The step S1 specifically refers to: Mix 8% to 16% by weight of phenol / diaminodiphenylmethane type benzoxazine monomer, 12% to 25% by weight of phenol / aldehyde type benzoxazine, 3% to 8% by weight of bisphenol A type epoxy resin, and 40% to 60% by weight of acetone solvent, and stir evenly; The stirring speed is 100 to 500 revolutions per minute. The stirring time is 10min to 30min.
4. The method for preparing a low-deformation, high-temperature-resistant, frequency-selective conformal radome according to claim 1, characterized in that: The step S2 specifically refers to: The QW100 quartz fiber cloth and the T300 carbon fiber cloth are fully impregnated in the resin glue solution respectively; Air-drying or drying in an oven to remove the acetone solvent, and preparing quartz fiber reinforced benzoxazine resin prepreg and carbon fiber reinforced benzoxazine resin prepreg; Among them, the drying temperature is 30°C to 60°C, and the drying time is 12h to 36h.
5. The method for preparing a low-deformation, high-temperature-resistant, frequency-selective conformal radome according to claim 1, characterized in that: The thermal curing of the product A in step S4 specifically refers to: Layer a porous isolation cloth, a non-porous isolation cloth and a breathable felt on the product A, seal the formed structure on the mold, place it in an autoclave for pre-pressing, and obtain an outer skin semi-cured part; Among them, the curing temperature is 120℃~160℃, and the curing time is 6h; The curing pressure is 0.3MPa~0.6MPa; The vacuum degree of the autoclave is 0~0.1MPa.
6. The method for preparing a low-deformation, high-temperature-resistant, frequency-selective conformal radome according to claim 1, characterized in that: When the activation film is laser etched in step S5, the laser light source is a near-infrared laser, the laser power is 20W to 600W, the pulse repetition frequency is 10Hz to 400KHz, the processing times are 2 to 6 times, the scanning speed is 5mm / s to 5000mm / s, and the scanning spacing is 0.006mm to 0.5mm.
7. The method for preparing a low-deformation, high-temperature-resistant, frequency-selective conformal radome according to claim 1, characterized in that: The step S6 specifically refers to: cleaning and removing the activation film, placing the laser-etched outer skin solidified part in a chemical plating solution, and depositing the conductive metal in the chemical plating solution to the laser-etched area of the antenna cover outer skin wave-transmitting window; wherein, metallic copper is first deposited in the laser-etched area, and then the gold layer is deposited.
8. The method for preparing a low-deformation, high-temperature-resistant, frequency-selective conformal radome according to claim 1, characterized in that: The step S7 of hot pressing and curing the product B specifically refers to: Sequentially lay a peelable cloth and a breathable felt on the product B, seal the formed structure on a mold, and place it in an autoclave for pre-pressing to obtain a blank; Among them, the curing temperature is 120℃~200℃, and the curing time is 10h; The curing pressure is 0.1MPa~0.8MPa; The vacuum degree of the autoclave is 0~0.1MPa.
9. The method for preparing a low-deformation, high-temperature-resistant, frequency-selective conformal radome according to claim 1, characterized in that: The fiber orientation angles of the fibers in ply A, ply B and ply C in the blank are 0° or 90°.